2012
DOI: 10.1007/s00259-012-2118-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of early and late residual 18F-fluorodeoxyglucose and 18F-fluorothymidine uptake using different SUV measurements in patients with non-small-cell lung cancer treated with erlotinib

Abstract: Early and late residual FDG uptake, measured using different quantitative SUV parameters, are predictive factors for short-term outcome in patients with advanced NSCLC treated with erlotinib. Additionally, low residual FDG and FLT uptake early and late in the course of erlotinib treatment is associated with improved PFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 16 publications
(32 reference statements)
1
27
0
Order By: Relevance
“…Several studies have shown that FDG-PET is a useful imaging modality for predicting response to erlotinib in patients with non-small cell lung cancer (NSCLC) [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. However, most of these studies used only the primary tumor as the target lesion for sequential imaging [3][4][5][6][7][8][9][10][11][12], and treatment response was largely assessed using the European Organization for Research and Treatment of Cancer (EORTC) criteria [3][4][5][6][7][8][9]20]. Other studies have evaluated treatment response using the Positron Emission Tomography Response Criteria in Solid Tumors (PERCIST) [21], based on the measurement of a specific focus on the hottest single lesion, including the metastatic tumor [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that FDG-PET is a useful imaging modality for predicting response to erlotinib in patients with non-small cell lung cancer (NSCLC) [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. However, most of these studies used only the primary tumor as the target lesion for sequential imaging [3][4][5][6][7][8][9][10][11][12], and treatment response was largely assessed using the European Organization for Research and Treatment of Cancer (EORTC) criteria [3][4][5][6][7][8][9]20]. Other studies have evaluated treatment response using the Positron Emission Tomography Response Criteria in Solid Tumors (PERCIST) [21], based on the measurement of a specific focus on the hottest single lesion, including the metastatic tumor [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Despite high sensitivity for staging lung cancer with 18 F-FDG PET compared to conventional imaging modalities, false-positive findings can occur, particularly in inflammatory lesions (4,5,10). Non-specific uptake by these non-malignant tissues resulted in a positive predictive value of 18 F-FDG PET in the pulmonary lesions as low as 44.6% (27). 18 F-FLT is an analog of thymidine and its uptake has been found PET, positron emission tomography; FLT, fluorothymidine; FDG, fluorodeoxyglucose; PLR, positive-likelihood ratio; NLR, negative-likelihood ratio; DOR, diagnostic odds ratio.…”
Section: Discussionmentioning
confidence: 99%
“…A pulmonary lesion is an extremely common and clinically challenging disorder in China, as well as in a number of other countries (27,28), and lung cancer is the first leading cause of tumor-related mortality. The differentiation of lung cancer from benign pulmonary lesions is a well-known diagnostic problem in daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to diagnosis and staging, FDG PET/CT is used to measure treatment response. Here residual FDG uptake or changes in uptake during or after treatment are used as predictive factors [4][5][6]. To this end, criteria to measure FDG uptake changes and/or metabolic response have been proposed [7,8].…”
mentioning
confidence: 99%